Dietary management in colorectal cancer prevention: a review - Yudi Kristanto; Angeline Rosa Hartono (Intisari Sains Medis, 2021)
Colorectal cancer (CRC) is still a health problem with a high incidence worldwide. Genetic factors and environmental factors are the etiology of colorectal cancer. Eating habits are one of the environmental factors that can be regulated so as to prevent colorectal cancer. Diet food in the development of colorectal cancer has an important role. Several studies in the last decade have shown an association between the consumption of several foods and nutrients and the risk of colorectal cancer in epidemiological and experimental studies.